Reciprocal relationship between contact and complement system activation on artificial polymers exposed to whole human blood. (January 2016) - Huang, Shan; Engberg, Anna E.; Jonsson, Nina; Sandholm, Kerstin; Nicholls, Ian A.; Mollnes, Tom Eirik; Fromell, Karin; Nilsson, Bo; Ekdahl, Kristina N.
Abstract: Background: Inappropriate and uncontrolled activation of the cascade systems in the blood is a driving force in adverse inflammatory and thrombotic reactions elicited by biomaterials, but limited data are available on the activation of the contact system by polymers and the present study was undertaken to investigate these mechanisms in established models. Methods: Polymer particles were incubated in (1) EDTA-plasma (10 mM) to monitor the adsorption of 20 selected proteins; (2) lepirudin-anticoagulated plasma to evaluate contact system activation, monitored by the formation of complexes between the generated proteases factor[F]XIIa, FXIa and kallikrein and the serpins C1-inhibitor [C1INH] and antithrombin [AT]; (3) lepirudin-anticoagulated whole blood to determine cytokine release. Results: Strong negative correlations were found between 10 cytokines and the ratio of deposited FXII/C1INH, generated FXIIa-C1INH complexes, and kallikrein-C1INH complexes. Formation of FXIIa-C1INH complexes correlated negatively with the amount of C3a and positively with deposited IgG. Conclusions: A reciprocal relationship was found between activation of the contact system and the complement system induced by the polymers studied here. The ratios of FXII/C1INH or C4/C4BP, adsorbed from EDTA-plasma are useful surrogate markers for cytokine release and inflammatory response to materials intended for blood contact.